## Ask Singapore Homework?

Upload a photo of a Singapore homework and someone will email you the solution for free.

## Question

secondary 2 | Maths

Anyone can contribute an answer, even non-tutors.

##### Amanda

chevron_right chevron_right

Pls help! thanks in advance

Date Posted: 8 months ago
Views: 53

### See 1 Answer

done {{ upvoteCount }} Upvotes
clear {{ downvoteCount * -1 }} Downvotes
##### Lim Teng Shuen Ernest's answer
124 answers (Tutor Details)
1st
Date Posted: 8 months ago
Amanda
8 months ago
How did you get y=-×+c ? then -1=-3+c
LIM TENG SHUEN ERNEST
8 months ago
As stated, the general equation for a straight line is y = m x + c where m and c are values to be determined.

Apply the gradient formula using x and y values from the two points given to get gradient = -1

m is the gradient, so substitute m = -1 in the general equation to get y = (-1)x + c

All points on a line must satisfy the line equation. Since (3, -1) is a point on the line, we can substitute x = 3, y = -1 into the equation to get

-1 = (-1)(3) + c

We then simplify and solve to get c = 2 and the final line equation y = -x + 2
Amanda
8 months ago
I see, thank you!